Penerapan Problem Based Learning Berbantuan E-Book Berbasis Komik untuk Meningkatkan Aktivitas dan Hasil Belajar IPA - Krisdiana Enrika Puteri (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Based on the results of learning observations conducted at Bareng 05 Public Elementary School, Malang City, it was found that the learning outcomes and student activity during science content learning were still not optimal. An alternative solution to this problem is the application of the Problem-Based Learning (PBL) model using comics in the form of e-books. This study uses a classroom action research model from Kemmis & Mc Taggart. Each research cycle consists of planning, acting & observing, reflecting, and revising plan stages. Each cycle carried out two learning activities. The results showed that the application of the Problem-Based Learning model assisted by comic-based e-books could increase the activities and learning outcomes of science content for fourth graders of Bareng Public Elementary School 05. Based on the results of this study, it was suggested that further researchers develop and research e-books as media Learning is made according to the material to be taught.